Biological effect of black phosphorus nanosheets on the interaction between SARS-CoV-2 S protein and ACE2. Issue 44 (4th November 2022) - Liu, Rui Rui; Zhai, Hong Lin; Shao, Hai Ping; Wang, Tian Hua
Abstract : The binding of the spike glycoprotein (S protein) in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to angiotensin-converting enzyme 2 (ACE2) is the main pathway that leads to serious coronavirus disease 2019 (COVID-19) infection. Abstract : The binding of the spike glycoprotein (S protein) in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to angiotensin-converting enzyme 2 (ACE2) is the main pathway that leads to serious coronavirus disease 2019 (COVID-19) infection. In the biomedical applications of various nanomaterials, black phosphorus nanosheets (BP) have been receiving increasing attention owing to their excellent characteristics. In this study, the biological effect of BP on the interaction between the S protein and ACE2 was investigated by molecular dynamics simulations. The results indicated that the ACE2 could be quickly and stably adsorbed on the BP surface by non-specific binding and retain its structural integrity. Compared with the case without BP, the interaction of the S protein bound to ACE2 adsorbed on the BP surface was greatly weakened, including hydrogen bonds, salt bridges, and van der Waals forces. This study not only reveals that BP could effectively obstruct the binding of S protein and ACE2, which may provide a potential and reasonable drug carrier to further enhance the curative effect of inhibitors against SARS-CoV-2 infection, but also presents a novel interference mechanism for protein–protein interactions caused by nanomaterials.